C-reactive protein flare predicts response to anti-PD-(L)1 immune checkpoint blockade in metastatic urothelial carcinoma. (May 2022) - Klümper, Niklas; Sikic, Danijel; Saal, Jonas; Büttner, Thomas; Goldschmidt, Franziska; Jarczyk, Jonas; Becker, Philippe; Zeuschner, Philip; Weinke, Maximilian; Kalogirou, Charis; Breyer, Johannes; Burger, Maximilian; et al.
Abstract: Purpose: Robust biomarkers to predict response to immune checkpoint blockade (ICB) in metastatic urothelial carcinoma (mUC) are still in demand. Recently, early C-reactive protein (CRP) kinetics and especially the novel CRP flare-response phenomenon has been associated with immunotherapy response. Methods: We conducted a multicentre observational study comprising 154 patients with mUC treated with ICB to evaluate the predictive value of a previously described on-treatment CRP kinetics: CRP flare responders (at least doubling of baseline CRP within the first month after initiation of ICB followed by a decline below baseline within three months), CRP responders (decline in baseline CRP by ≥ 30% within three months without a prior flare) and the remaining patients as CRP non-responders. CRP kinetics groups were correlated with baseline parameters, PD-L1 status, progression-free survival (PFS) and overall survival (OS). Results: Objective response was observed in 57.1% of CRP responders, 45.8% of CRP flare responders and 17.9% of CRP non-responders ( P < 0.001). CRP flare response was associated with prolonged PFS and OS ( P < 0.001). In multivariable Cox regression analysis, CRP flare responders showed a risk reduction of ∼70% for tumour progression and death compared to CRP non-responders. Subgroup analysis of CRP flare responders revealed that patients with a long-flare response (completed flare-response kinetics ≥6 weeks on-treatment) showed even more favourable outcomes following ICB (HR = 0.18, 95%-CI: 0.07–0.48, P < 0.001). Conclusion: CRP (flare)response robustly predicts immunotherapy response and outcomes in mUC independent of PD-L1 status. Thus, early on-treatment CRP kinetics is a promising low-cost and easy-to-implement biomarker to optimise therapy monitoring in patients with mUC treated with ICB. Highlights: On-treatment CRP kinetics with predictive potential occur in mUC patients. CRP flare response predicts immunotherapy response and improved PFS and OS. CRP kinetics (especially CRP flare response) outperforms PD-L1 status. CRP long flare response associates with even improved ICB response rates.